Transition metal complex dye-sensitized 3D iodoplumbates: syntheses, structures and photoelectric properties. Issue 48 (24th May 2019) - Yue, Cheng-Yang; Yue, Yun-Di; Sun, Hai-Xiao; Li, Dong-Yang; Lin, Na; Wang, Xin-Ming; Jin, Ying-Xue; Dong, Yu-Han; Jing, Zhi-Hong; Lei, Xiao-Wu
Abstract : The first types of transition metal complex cationic dye-sensitized 3D hybrid porous iodoplumbates exhibiting outstanding visible light-driven photoelectric properties. Abstract : Here, we prepared the first series of 3D hybrid iodoplumbates with novel porous frameworks of [Pb8 I21 ] 5− directed by transition metal complex (TMC) cationic dyes of [TM(2.2-bipy)3 ] 2+ . The microporous materials exhibit outstanding visible light-driven photoelectric properties due to the effective photosensitization of the TMC dyes. The coexistence of stronger face- and weaker corner-shared connecting manners affords the feasibility of tailoring the 3D framework into low-dimensional skeletons, which provide a new structural prototype to modify the semiconducting properties similar to those of classic perovskites.